Emotion Regulation and Complex Brain Networks: Association Between Expressive Suppression and Efficiency in the Fronto-Parietal Network and Default-Mode Network - Pan, Junhao; Zhan, Liying; Hu, ChuanLin; Yang, Junkai; Wang, Cong; Gu, Li; Zhong, Shengqi; Huang, Yingyu; Wu, Qian; Xie, Xiaolin; Chen, Qijin; Zhou, Hui; et al. (Frontiers in Human Neuroscience, 2018)
Emotion regulation refers to the "implementation of a conscious or non-conscious goal to start, stop or otherwise modulate the trajectory of an emotion" (Etkin et al., 2015). Whereas multiple brain areas have been found to be involved in emotion regulation, relatively little is known about whether and how emotion regulation is associated with the global functioning of brain networks. Recent advances in brain connectivity research using graph-theory based analysis have shown that the brain can be organized into complex networks composed of functionally or structurally connected brain areas. Global efficiency is one graphic metric indicating the efficiency of information exchange among brain areas and is utilized to measure global functioning of brain networks. The present study examined the relationship between trait measures of emotion regulation (expressive suppression and cognitive reappraisal) and global efficiency in resting-state functional brain networks (the whole brain network and ten predefined networks) using structural equation modeling. The results showed that expressive suppression was reliably associated with efficiency in the fronto-parietal network and default-mode network. The finding advances the understanding of neural substrates of emotion regulation, revealing the relationship between expressive suppression and efficient organization of brain networks.